1993
DOI: 10.1042/bj2920673
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) transfer into metallothionein mediated by glutathione

Abstract: Rabbit liver metallothionein depleted of Cd(II) and Zn(II) was fully reconstituted using a Cu(I)-GSH complex under strictly anaerobic conditions. Anaerobic fluorescence titration, using an emission band at 625 nm which is diagnostic of the correct insertion of Cu(I) into the thiolate clusters of metallothionein, showed that the fluorescence maximum was obtained on addition of as many Cu(I) equivalents as the available Cu(I)-binding sites in the protein (i.e. 12). Binding was nearly complete within 1 min, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…Glutathione also plays an important role in Cu sequestration and detoxification in vivo (40,42,43). In cell-free systems, Cu(I) complexes of GSH have been shown to transfer Cu to both metallothionein (47) and to SOD1 (37)(38)(39). As such, it is possible that Cu(I)-GSH may also serve as a Cu donor for human SOD1 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione also plays an important role in Cu sequestration and detoxification in vivo (40,42,43). In cell-free systems, Cu(I) complexes of GSH have been shown to transfer Cu to both metallothionein (47) and to SOD1 (37)(38)(39). As such, it is possible that Cu(I)-GSH may also serve as a Cu donor for human SOD1 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that depletion of GSH results in greater intracellular levels of highly reactive unbound Cu that are able to generate further toxic ROS. This is supported by studies showing GSH to be important for cellular Cu transport, detoxification, and sequestration to metalloproteins and to the important antioxidant enzyme CuIZn SOD (Freedman et al, 1989;Ferreira et al, 1993;Vulpe and Packman, 1995). The role of free radicals in Cu toxicity was confirmed by abolition of toxicity using the H,O, and 0,-scavenger MnTMPyP (Day et al, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…This tripeptide is critical for removal of H202 and prevention against and repair of lipid and protein oxidation (Mark et id., 1997) and is an important Cu transport and detoxification molecule (Freedman e t al., 1989;Ferreira et al, 1993;Vulpe and Packman, 1995). GSH levels are maintained by a complex pathway involving y-glutamylcysteine synthetase (GS; EC 6.3.2.2), glutathione peroxidase (GPx; EC 1.1 1.1.9), and glutathione reductase (GR; EC 1.6.4.2) (Bains and Shaw, 1997 …”
mentioning
confidence: 99%
“…It has long been suggested that reduced glutathione (GSH) may participate in intracellular Cu homeostasis by forming Cu-GSH complexes when transferring Cu to CSD (Ciriolo et al, 1990) and metallothionein (Ferreira et al, 1993) in vitro. GSH was required for CCS-independent activation of hSOD1 in yCCS mutant strains with defective GSH metabolism, and wSod-1 was inactive in the presence of CCS when GSH was depleted in yeast (Carroll et al, 2004;Jensen and Culotta, 2005).…”
mentioning
confidence: 99%